Characterizing the variability of transit time distributions and young water fractions in karst catchments using flux tracking. Issue 15 (17th June 2020) - Zhang, Zhicai; Chen, Xi; Cheng, Qinbo; Soulsby, Chris
Abstract: Hydrological and biogeochemical processes in karst environments are strongly controlled by heterogeneous fracture‐conduit networks. Quantifying the spatio‐temporal variability of water transit time and young water fractions in such heterogeneous hydrogeological systems is fundamental to linking discharge and water quality dynamics in the karst critical zone. We used a tracer‐aided conceptual hydrological model to track the fate of each hour of rain input individually. Using this approach, the variability of transit time distributions and young water fraction were estimated in the main landscape units in a karst catchment of Chenqi in Guizhou Province, Southwest China. The model predicted that the mean young water (i.e., <~2 months old) fraction of ground conduit flow is 0.31. Marked seasonal variabilities in water storage and hydrological connectivity between the conduit network and fractured matrix, as well as between hillslopes and topographic depression, drive the dynamics of young water fraction and travel time distributions in each landscape unit. Especially, the strong hydrological connectivity between the land surface and underground conduits caused by the direct infiltration through large fractures and sinkholes, leads the drastic increasement in young water fraction of runoff after heavy rain. Even though the contribution of young water to runoff is greater, the strong mixing and drainage of small fractures accelerate the old water release during high flows during the wet season. It is notable that the young water may sometimes be the most contaminated component contributing to the underground conduit network in karst catchments, because of the direct transfer of contaminants from the ground surface with rain water via large fractures and sinkholes. Abstract : The tracer‐aided hydrological model can be used to assess the spatio‐temporal variability of water transit time and young water fractions in karst critical zone. Strong hydrological connectivity between the land surface and underground conduits leads the drastic increasement in young water fraction of runoff after heavy rain. Strong mixing and drainage of small fractures accelerate the old water release during high flows.